(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the effectiveness and the adverse effects of electroacupuncture and acupressure massage combined with heated mugwort compress in improving activities of daily living in patients with acute low back pain. Methods: A controlled interventional clinical study, compare before and after treatment. 60 patients were divided into 2 equal groups, the study group was administered electroacupuncture and acupressure massage combined with heated mugwort compress; the control group was administered electro acupuncture and acupressure massage combined with infrared radiation. Results: After treatment, the activities of daily living according to the ODI score in the study group decreased from 11.47 ± 2.03 points to 4.60 ± 2.60 points, which was significantly lower than that in the control group (p < 0.05). The overall treatment outcomes were 56.7% good, 16.7% fair, and 26.7% average, which were better than those of the control group (p < 0.05). No clinically observed adverse effects were recorded during the 14-day treatment period. Conclusions: Electroacupuncture and acupressure massage combined with mugwort compress are effective in improving activities of daily living and do not cause adverse effects in patients with acute low back pain.